Transcription factor NRF2 protects mice against dietary iron-induced liver injury by preventing hepatocytic cell death - Silva-Gomes, S (2014)
BACKGROUND & AIMS: The liver, being the major site of iron storage, is particularly exposed to the toxic effects of iron. Transcription factor NRF2 is critical for protecting the liver against disease by activating the transcription of genes encoding detoxification/antioxidant enzymes. We aimed to determine if the NRF2 pathway plays a significant role in the protection against hepatic iron overload.METHODS: Wild-type and Nrf2(-/-) mouse primary hepatocytes were incubated with ferric ammonium citrate. Wild-type and Nrf2(-/-) mice were fed standard rodent chow or iron-rich diet for 2weeks, with or without daily injection of the antioxidant mito-TEMPOL.RESULTS: In mouse hepatocytes, iron induced the nuclear translocation of NRF2 and the expression of cytoprotective genes in an NRF2-dependent manner. Moreover, Nrf2(-/-) hepatocytes were highly susceptible to iron-induced cell death. Wild-type and Nrf2(-/-) mice fed iron-rich diet accumulated similar amounts of iron in the liver and were equally able to increase the expression of hepatic hepcidin and ferritin. Nevertheless, in Nrf2-null mice the iron loading resulted in progressive liver injury, ranging from mild confluent necrosis to severe necroinflammatory lesions. Hepatocytic cell death was associated with gross ultrastructural damage to the mitochondria. Notably, liver injury was prevented in iron-fed animals that received mito-TEMPOL.CONCLUSIONS: NRF2 protects the mouse liver against the toxicity of dietary iron overload by preventing hepatocytic cell death. We identify NRF2 as a potential modifier of liver disease in iron overload pathology and show the beneficial effect of the antioxidant mito-TEMPOL in a mouse model of dietary iron-induced liver injury.